Automated Detection of Asbestos-cement Roofs Using Multi-source Remote Sensing Data and Machine Learning - Durczak, Kacper; Janicka, Joanna; Błaszczak-Bąk, Wioleta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Asbestos, due to its resistance to temperature, chemicals, and mechanical damage, was widely used in construction, especially in the second half of the 20th century. Today, most of the remaining asbestos products are roofing sheets, which pose a serious health risk and the WHO calls for its elimination. One of the key actions is to identify buildings with asbestos-cement roofing.
Keywords: asbestos; machine learning; LIDAR